Comparison of schedule delay and causal factors between traditional and green construction projects - Hwang, Bon Gang; Leong, Lay Peng (Technological and Economic Development of Economy, 2013)
Despite the heighten focus on environmental sustainability for green construction, rare research has been conducted to analyze such projects, especially in the aspect of their schedule delay and causal factors. Conducting a survey in which 30 companies in the Singapore construction industry participated, this study first identified the degree of project delay in 220 traditional and 96 green construction projects performed in Singapore. Next, a set of factors affecting project delay was identified based on various literatures to determine the most influential factors for both green and traditional projects. The analysis result established that 15.91% of the traditional projects were delayed while 32.29% of the green construction projects were completed behind schedule. Furthermore, the top 5 factors causing delay in green projects were: (1) speed of decision making by client; (2) speed of decision making involving all project teams; (3) communication/coordination between key parties; (4) level of experience of consultants; and (5) difficulties in financing project by contractors. Lastly, recommendations were introduced to reduce schedule delay in green construction projects based on the analysis results. This study will serve as s a base for further research on the enhancement of green construction schedule performance.